SEMINAR PEMANFAATAN APLIKASI CANVA DALAM MEMBUAT MEDIA PEMBELAJARAN INOVATIF DI DESA SUKABUNGAH - Zulfan, Salman Ulwan; Sugiharti, Rini Endah; Rikmasari, Rima (Universitas Islam 45 Bekasi, 2024)
Rapid advancements in education have been driven by technological progress, replacing traditional methods such as lectures and handwritten notes. It is noted that technology, particularly Artificial Intelligence (AI), has transformed the way learning occurs. The evolution of learning from traditional methods towards utilizing technology in the educational process poses a challenge for teachers, especially in Sukabungah village where not all teachers are currently proficient in operating Information technology to create educational media/learning materials. This writing originated from a training seminar aimed at showcasing the utilization of Canva for creating innovative learning media to elementary school teachers in the Bojongmangu Subdistrict. The objective of this engagement, in the form of a seminar, is to enhance innovative and creative learning by utilizing Canva-based learning media that aligns with the learning environment. Present-day learning demands teachers to adapt to technology. Based on the findings of this research, utilizing the Canva application in teaching is encouraged so that educators are expected to adapt to current technology trends, specifically by employing Canva for teaching and learning. Canva facilitates educators in delivering innovative and creative teaching materials.